Diseño de una máquina para rectificar las pestañas de rines en acero, para automóviles (2017)
The manufacture of the machine and a financial evaluation to know the viability of the project. A problem is identified in the process of repairing wheels in steel for automobiles, reason why arises the necessity to design a machine for this purpose; The automotive market is studied and information is collected regarding the grinding process of wheels and with this information the search process begins, selection and development of alternatives for the design of the machine, later the detailed design is carried out developing engineering calculations to be Verified by means of finite element software and the financial study with all the expenses that would carry out the machine.